1983
DOI: 10.1002/bjs.1800700224
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of Nissen fundoplication and Boerema gastropexy in the surgical treatment of gastro-oesophageal reflux in children

Abstract: The results of surgical treatment of gastro-oesophageal reflux in 133 infants and children clearly demonstrated the superiority of the Nissen fundoplication over the Boerema gastropexy. The failure to control reflux in the gastropexy group (50 patients) was 42 per cent compared with a 9.6 per cent failure rate in the fundoplication group (83 patients). This resulted in a reoperation rate of 24 per cent for the gastropexy procedure compared with 8 per cent for the fundoplication. There was no difference in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Our overall complication rate of 23% and the postoperative death rate are difficult to compare with other studies (2,4‐8). In the latter studies, the patients included were heterogeneous with regard to age, severity of GERD, indication for operation, presenting symptoms, associated conditions and duration of follow‐up.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…Our overall complication rate of 23% and the postoperative death rate are difficult to compare with other studies (2,4‐8). In the latter studies, the patients included were heterogeneous with regard to age, severity of GERD, indication for operation, presenting symptoms, associated conditions and duration of follow‐up.…”
Section: Discussionmentioning
confidence: 62%
“…The allegedly poor reputation of anterior gastropexy is therefore not sustained by our results. The explanation for the high recurrence rate after gastropexy in other series (2,9) is probably a matter of technical detail. Adequate dissection of the esophagus in the hiatus and mobilization of a 5-cm segment into the abdomen is essential to obtain a high pressure zone.…”
Section: Fig 2 Percentage Of Patients Without Recurrence Of Symptoms ...mentioning
confidence: 95%
See 2 more Smart Citations
“…We observed postoperative comphcations in 3 children (13.6%) and all complications were managed non-operatively. In contrast, De Laet reported a complication rate of 24.8 % for Boerema and Nissen fundoplications in children and Turnage reported a complication rate of 45 % for Nissen fundoplications in infants and children (5,19). Wilkins reported in 1987 an adhesion obstruction rate of 10.3 % foilowing Nissen fundoplications in children and warned that "presenting symptoms were not typical of intestinal obstruction because many children were unable to vomit" and she found that only 3 of these 16 patients (19 %) did vomit but all had radiological appearances suggestive of small bowel obstruction (22).…”
Section: Discussionmentioning
confidence: 95%